Challenges and Pre-Conditions of Green Financing Development - G. M. Magomedova (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The article deals with an acute topic connected with sustainable development, i. e. the development of green financing. Raising capital for green investment was limited due to micro-economic problems dealing with internationalization of external factors, informational asymmetry, inadequate analytical potential and vague definition of the notion ‘green’. Green bonds mean various debt tools, after flotation of which earnings go to financing or refinancing of effective or new green projects. The article describes stages of green bond market development, characterizes participants of this trend and shows voluntary standards of green bonds that should be used for their issuance. The principle goals of green finance are to internationalize ecological external factors and reduce risk perception, to stimulate investment that could provide ecological advantages. The author studies benefits and structure of green bonds by aims of using profits and shows pre-conditions of green financing development. They are creation of favorable environment, support of business climate, provision of bank regulation bodies with authorities to supervise ecological risks of the finance sector and law supremacy and investment regime, which could promote growth in green investment activity.